Problems of Criminal Law Evidence in Murder and Sexual Violence Cases (Case Study of Vina Cirebon Murder) - Kinanti Puput Septiana; Harefa, Beniharmoni (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2024)
The issue of evidence in the case of murder and sexual violence against Vina in Cirebon has become an obstacle in the case resolution process. This issue can lead to errors in identity or wrongful arrests, creating legal uncertainty and reducing public trust in the justice system, thereby hindering the effective enforcement of justice. The purpose of this research is to understand the evidentiary process in law enforcement regarding the perpetrators of murder and sexual violence in this case, and to examine the responsibility of law enforcement for errors in identity caused by evidentiary problems. The research method used is normative juridical, analyzing legal sources such as laws, court decisions, legal theories, and expert opinions. The findings show that there were evidentiary issues in this case, including witness testimony, the defendant's testimony, results from the visum et repertum, and exhumation. Furthermore, the responsibility of law enforcement for errors in identity can be linked to Articles 95-97 of Law No. 8 of 1981 concerning the Criminal Procedure Code. The police, as law enforcement officers, can also be subject to sanctions under Article 7 paragraph (1) letter c of the National Police Chief Regulation No. 14 of 2011 concerning the Code of Ethics for the Indonesian National Police and Article 7 of Government Regulation No. 2 of 2003 concerning the Disciplinary Regulations for Members of the Indonesian National Police. Errors in identity in this case highlight the importance of thoroughness in the evidentiary process to ensure that justice is properly served.